Re-Examining the Role of Business Associations in Russia and Post-Communist Countries: From Interest Groups to Defensive Organizations - Kazun, Anton (Journal of Economic Sociology, 2015)
In Building Business in Post-Communist Russia, Eastern Europe, and Eurasia: Collective Goods, Selective Incentives, and Predatory States Dinissa Duvanova discusses a “theory of defensive organizations”. Duvanova proposes this theory as an alternative to the theory of interest groups by Olson, Stigler et al. The theory of defensive organizations arises from the critique of the view of business associations as lobbyists caring only for their own interests. Duvanova uses quantitative data from 27 countries in Eastern Europe and Eurasia and qualitative data about the situation in Russia, Ukraine, Croatia and Kazakhstan in order to show that the experience of post-communist countries does not correspond to the predictions of the theory of interest groups. The author sets out to examine and counter the following myths about business associations, including: (1) business associations are a consequence of good institutions; (2) they are not needed in countries with the high level of corruption; (3) they act as cartels seeking to price collusion; (4) compulsory membership in the business associations may solve the collective action problem. Duvanova concludes that business associations in Russia and in other countries of Eastern Europe and Eurasia protect their members from a predatory state rather than from a free market. The review notes some limitations of the book: 1) a relatively short period of quantitative analysis (six-year period from 1999 to 2005); 2) an insufficient account of the differences within the countries; and 3) the excessive optimism of the theory. In general, Duvanova proposes a theory which has high explanatory potential, which will be useful for further empirical research. She consciously simplifies the explanatory scheme to offer a formal model that can be applied to problems beyond the scope of this book. Furthermore, the reviewer notes that the theory of defensive organizations does not contradict the theory of interest groups, rather it expands and complements this theory for countries with a recently developing business community.